Kawasaki disease in ghana: case reports from Korle Bu teaching hospital - Badoe, E.V.; Neequaye, J.; Oliver-Commey, J.O.; Amoah, J.; Osafo, A.; Aryee, I.; Nyarko, M.Y. (Ghana medical journal, 2011)
Kawasaki disease, an acute febrile vasculitis, predominantly affects children under the age of 5 years and is thought to be a rare disease in the developing world. It has previously never been reported in Ghana. We report 3 cases from February, 2007 to February, 2008. This potentially serious disease has no definitive diagnostic test and it is not unusual for diagnosis to be delayed with serious consequences. Any child with irritability and persisting fever (>5 days) not responding to antipyretics and antibiotics, accompanied by a rash and non purulent conjunctivitis should be suspected to have Kawasaki disease.